Effect of early feeding of diluted diets on haematology and serum chemistry of exotic and improved local chicks - Sola-Ojo, F.E; Alli, O.I; Adeyemi, K.D; Akinjuku, J.O (Nigerian Journal of Animal Science, 2023)
An experiment was conducted to evaluate the haematology and serum biochemistry of exotic and improved local chicks fed different diluted diets at early age (0 – 4 weeks). Two hundred (200) day old chicks (exotic and improved local genotype) were used for this study. The chicks were wing tagged and grouped at random based on genotypes to four dietary treatments. The diets were; commercial diets (CD) as Control, CD + 20% wheat offal (CDW), CD + 20% palm kernel cake (CDP) and CD + 20% processed baobab seed meal (CDB). At four weeks of age, blood samples were taken from the chicks for serum and haematological assay. The results indicated that packed cell volume, white blood cell, red blood cell, lymphocyte, neutrophil, monocyte, eosinophil and basophil were similar (p < 0.05) irrespective of the chicks’ genotype and across the dietary treatments. Significant (p < 0.05) variations existed in haemoglobin value between the strains and across the dietary treatment (2.45 to 8.80 x 106g/dl-1 ). Alanine aminotransferase and uric acid were not significantly influenced (p> 0.05) by genotypes and diets, but glucose, protein, albumin, cholesterol, alkaline phosphatase, aspartate aminotransferase, creatinine, high density lipoprotein, low density lipoprotein and triglycerol significantly (p < 0.05) varied. Dilution of chicks’ diets should be discouraged because it had a significant negative effect on haemoglobin and caused significant variations in chicks serum chemistry